Pemanfaatan Cyber Notary Terhadap Digitalisasi Akta - Ulang, Andi Dala; Magassing, Abdul Maasba; Sakharina, Iin Karita (Universitas Widya Gama Malang, 2023)
This research aims to analyze the use of digitizing authentic deeds by Notaries in Makassar City and to analyze the legal certainty of the principles of agreements between the parties in digitizing authentic deeds by Notaries. This research is empirical research, where the data is qualified as primary and secondary data. Primary data was obtained through interviews, and secondary data was obtained through literature study. The data collected was then processed using a qualitative analysis approach. The research results show that the use of digitalization of authentic deeds by Notaries in Makassar City will basically really help the work of Notaries and also the parties, namely it can save time and costs compared to conventionally making authentic deeds. However, because until now there is no legal umbrella and it is considered contradictory, no Notary in Makassar has ever digitized an authentic deed. And then the legal certainty of the principle of agreement between the parties in digitizing an authentic deed by a Notary based on positive law in Indonesia is that it does not have perfect proof like an authentic deed, this is because the digitization of the Notary's deed does not meet the requirements for the authenticity of a deed.